Phenotype Profiling and Allergy in Otitis-Prone Children - Torretta, Sara; Pignataro, Lorenzo; Carioli, Daniela; Ibba, Tullio; Folino, Francesco; Rosazza, Chiara; Fattizzo, Miriam; Marchisio, Paola (Frontiers in Pediatrics, 2018)
Background: Otitis-prone children can present some distinctive clinical patterns and although a number of known risk factors for recurrent acute otitis media (RAOM) are known, no dedicated epidemiological models have been developed to explain clinical heterogeneity. Methods: A preliminary retrospective pilot study was planned to evaluate the possible effect of allergic disease in the development of different disease phenotypes in otitis-prone children aged 3-10 years, particularly the absence (simple RAOM), or presence of episodes of otitis media with effusion between acute infections (RAOM with OME). Results: Analysis was based on the data contained in 153 charts (55.6% males, mean age of 59.4 ± 16.4 months). 75.8% of children had a simple RAOM and 24.2% a RAOM with OME. Atopy or allergy were documented in respectively 47.7% and 41.3% of children considered as a whole. The prevalence of atopy or allergy was significantly higher in the children with a RAOM with OME (atopy: 73.0% vs 39.5%, p<0.001; allergy: 60.0% vs 36.1%, p=0.049), who also more frequently showed adenoidal hypertrophy (p=0.016), chronic adenoiditis (p=0.007), conductive hearing loss (p=0.004), and impaired tympanometry (p<0.001). Conclusions: These data suggest that children with a RAOM with OME are clinically different from children with simple RAOM, as they have a more complex clinical presentation that includes not only adenoidal disease and audiological impairment, but also an underlying allergy or atopy. The possibility that the factors mentioned above may be differently involved in the heterogeneous clinical manifestations occurring in otitis-prone children needs to be further investigated in ad hoc epidemiological studies.